Surface-treated copper foil, copper-clad laminate, and printed wiring board
By forming a specific surface treatment layer on the surface of the copper foil, the problems of conductor loss and poor adhesion in the high-frequency electrical signal environment are solved, and excellent adhesion between the copper foil and the resin substrate and solder heat resistance are achieved.
Patent Information
- Application Number
- CN202380050111.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-28
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-14
AI Technical Summary
In a high-frequency electrical signal environment, the increase in the roughness of the copper foil surface leads to an increase in conductor loss, and the poor adhesion between the low-dielectric resin substrate and the copper foil is affected, affecting the solder heat resistance of the circuit pattern.
By forming a surface treatment layer on the surface of the copper foil, the volume Vmp of the solid part of the mountain is controlled to be within the range of 0.010 to 0.080 μm3/μm2, and the Zn adhesion amount is controlled to be within the range of 10 to 250 μg/dm2 to improve the copper foil and resin substrate. and heat resistance of solder.
The adhesion between the copper foil and the resin substrate is improved, and it is particularly suitable for high-frequency applications, and the formed circuit pattern has excellent solder heat resistance.
Smart Images

Figure CN119452124A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a surface treated copper foil, a copper clad laminate and a printed circuit board. Background Art
[0002] Copper clad laminates are widely used in various applications such as flexible printed wiring boards. Flexible printed wiring boards are manufactured by etching the copper foil of a copper clad laminate to form a circuit pattern (also called a "conductor pattern"), and then connecting and mounting electronic components on the circuit pattern using solder.
[0003] In recent years, the high frequency of electrical signals in electronic devices such as personal computers and mobile terminals has been continuously developing along with the high speed and large capacity of communication, and flexible printed circuit boards that can cope with this situation are required. In particular, the higher the frequency of the electrical signal, the greater the loss (attenuation) of the signal power, and the more difficult it is to read the data. Therefore, it is required to reduce the loss of signal power.
[0004] The causes of signal power loss (transmission loss) in electronic circuits can be roughly divided into two categories. The first is conductor loss, which is the loss caused by copper foil. The second is dielectric loss, which is the loss caused by the resin base material.
[0005] In the high-frequency region, the current has the characteristic of flowing on the surface of the conductor (i.e., the skin effect). Therefore, if the surface of the copper foil is rough, the current will flow along a complex path. Therefore, in order to reduce the conductor loss of high-frequency signals, it is ideal to reduce the surface roughness of the copper foil.
[0006] Hereinafter, in this specification, when simply describing “transmission loss” and “conductor loss”, these mainly refer to “transmission loss of high-frequency signals” and “conductor loss of high-frequency signals”.
[0007] Dielectric loss depends on the type of resin substrate. Therefore, in a circuit substrate where high-frequency signals flow, it is desirable to use a resin substrate formed of a low-dielectric material (e.g., liquid crystal polymer, low-dielectric polyimide). In addition, dielectric loss is also affected by the adhesive used to bond the copper foil to the resin substrate. Therefore, it is desirable to bond the copper foil to the resin substrate without using an adhesive.
[0008] Therefore, it has been proposed to form a surface treatment layer on at least one side of the copper foil in order to bond the copper foil to the resin substrate without using an adhesive. For example, Patent Document 1 proposes the following method: a roughening treatment layer formed of roughening particles is provided on the copper foil, and a silane coupling treatment layer is formed on the outermost layer.
[0009] [Prior art literature]
[0010] [Patent Document]
[0011] [Patent Document 1] Japanese Patent Application Publication No. 2012-112009. Summary of the invention
[0012] [Problems to be Solved by the Invention]
[0013] If the copper foil surface is roughened, the anchoring effect caused by the roughened particles can improve the adhesion between the copper foil and the resin substrate, but sometimes the conductor loss increases due to the skin effect. Therefore, it is ideal to reduce the roughened particles electrodeposited on the copper foil surface.
[0014] On the other hand, if the coarsening particles deposited on the surface of the copper foil are reduced, the anchoring effect brought by the coarsening particles is reduced. As a result, the adhesion between the copper foil and the resin substrate cannot be fully obtained. In particular, the resin substrate formed by low dielectric materials such as liquid crystal polymers and low dielectric polyimides is difficult to adhere to the copper foil compared to the previous resin substrates, so it is desired to develop a method to improve the adhesion between the copper foil and the resin substrate.
[0015] Furthermore, although the silane coupling treatment layer has the effect of improving the adhesion between the copper foil and the resin substrate, the effect of improving the adhesion may be insufficient depending on the type of the layer.
[0016] Furthermore, in the circuit pattern formed by etching the copper foil of the copper clad laminate, electronic components are usually assembled by soldering, but as the circuit pattern becomes finer in pitch, it is difficult to ensure the reliability of the connection with the electronic components. In particular, there are cases where the circuit pattern sometimes melts during soldering and the solder heat resistance is not sufficient.
[0017] The embodiment of the present invention is completed to solve the above-mentioned problems. In one embodiment, the embodiment of the present invention aims to provide a surface-treated copper foil which can improve the adhesion with a resin substrate, especially a resin substrate suitable for high-frequency applications, and form a circuit pattern with excellent solder heat resistance.
[0018] In another embodiment of the present invention, the object is to provide a copper-clad laminate, wherein the resin substrate, especially the resin substrate suitable for high-frequency applications, has excellent adhesion to the surface-treated copper foil and can form a circuit pattern with excellent solder heat resistance.
[0019] Furthermore, in another embodiment of the present invention, an object is to provide a printed wiring board having a circuit pattern with excellent solder heat resistance and having excellent adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and the circuit pattern.
[0020] [Technical means to solve the problem]
[0021] In order to solve the above-mentioned problems, the inventors of the present invention have conducted intensive research on surface-treated copper foil, and found that the solid volume Vmp of the mountain portion of the surface treatment layer is related to the complexity of the shape of the surface treatment layer (especially the roughened particles in the roughening treatment layer). By controlling the solid volume Vmp of the mountain portion of the surface treatment layer to a specified range, the anchoring effect brought by the surface treatment layer can be enhanced, thereby improving the adhesion between the surface-treated copper foil and the resin substrate.
[0022] The present inventors have also found that the amount of Zn deposited in the surface treated layer is related to the solder resistance of the circuit pattern formed of the surface treated copper foil, and that the solder resistance of the circuit pattern can be improved by controlling the amount of Zn deposited within a predetermined range.
[0023] The embodiments of the present invention have been completed based on this knowledge.
[0024] That is, in one embodiment, the embodiment of the present invention relates to a surface-treated copper foil, which comprises a copper foil and a surface-treated layer formed on at least one side of the copper foil, wherein the volume Vmp of the substantial part of the mountain portion of the surface-treated layer is 0.010 to 0.080 μm 3 / μm 2 , and the Zn adhesion is 10~250μg / dm 2 .
[0025] Moreover, in another example, the embodiment of the present invention relates to a copper-clad laminate including the surface-treated copper foil and a resin substrate of the surface-treated layer subsequent to the surface-treated copper foil.
[0026] Furthermore, in another example, the embodiment of the present invention relates to a printed wiring board including a circuit pattern formed by etching the surface-treated copper foil of the copper-clad laminate.
[0027] [Effects of the Invention]
[0028] According to an embodiment of the present invention, in one example, a surface-treated copper foil can be provided, which can improve adhesion with a resin substrate, especially a resin substrate suitable for high-frequency applications, and form a circuit pattern with excellent solder heat resistance.
[0029] Furthermore, according to an embodiment of the present invention, in another example, a copper-clad laminate can be provided, wherein the resin substrate, especially a resin substrate suitable for high-frequency applications, has excellent adhesion to the surface-treated copper foil and can form a circuit pattern with excellent solder heat resistance.
[0030] Furthermore, according to an embodiment of the present invention, in another example, a printed wiring board can be provided, which has a circuit pattern with excellent solder heat resistance and excellent adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and the circuit pattern. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] [ Figure 1 ] is a graph showing a typical load curve of a surface treatment layer.
[0032] [ Figure 2 ] is a cross-sectional view schematically showing an example of an implementation scheme of the present invention, namely, a surface-treated copper foil having a roughening treatment layer on one side of the copper foil. DETAILED DESCRIPTION
[0033] Hereinafter, the preferred embodiments of the present invention will be specifically described, but the present invention should not be limited to these embodiments for interpretation, and various changes and improvements can be made based on the knowledge of the industry as long as it does not deviate from the main purpose of the present invention. The multiple components disclosed in the following embodiments can form various inventions by appropriate combination. For example, several components can be deleted from all the components shown in the following embodiments, and the components of different embodiments can be appropriately combined.
[0034] The surface-treated copper foil according to the embodiment of the present invention comprises a copper foil and a surface-treated layer formed on at least one surface of the copper foil, wherein the surface-treated layer has a substantial volume Vmp of 0.010 to 0.080 μm at the peaks. 3 / μm 2 , and the Zn adhesion is 10~250μg / dm 2 .
[0035] According to the above configuration, it is possible to realize a surface-treated copper foil which can improve adhesion with a resin substrate, particularly a resin substrate suitable for high-frequency applications, and form a circuit pattern having excellent solder heat resistance.
[0036] The surface treatment layer may be formed on only one side of the copper foil or on both sides of the copper foil. When the surface treatment layer is formed on both sides of the copper foil, the types of the surface treatment layers may be the same or different. When the types of the surface treatment layers formed on both sides of the copper foil are different, for example, the surface treatment layer including the roughening treatment layer is formed on one side of the copper foil, and the surface treatment layer not including the roughening treatment layer is formed on the other side of the copper foil.
[0037] The surface shape of the surface treatment layer can be determined using surface texture parameters. The surface texture parameters can be obtained by measuring the surface shape in accordance with ISO 25178-2:2012 and analyzing the load curve calculated from the measured data.
[0038] When explaining the load curve, first, the load area ratio will be explained.
[0039] The so-called load area ratio refers to the ratio obtained by dividing the area corresponding to the cross section of the three-dimensional measurement object by the area of the measurement field when the three-dimensional measurement object is cut at a certain height. In the present invention, the measurement object is assumed to be a copper foil or a surface treatment layer of a surface-treated copper foil.
[0040] The load curve is a curve showing the load area ratio at each height. The height near the load area ratio of 0% shows the height of the highest part of the measurement object. The height near the load area ratio of 100% shows the height of the lowest part of the measurement object.
[0041] Figure 1 This is a graph showing a typical load curve of a surface treatment layer.
[0042] The load curve can be flexibly applied to express the solid volume and space volume of the surface treatment layer. The so-called solid volume is equivalent to the volume of the part occupied by the solid part of the measured object under the measurement field of view. The so-called space volume is equivalent to the volume occupied by the space between the solid parts under the measurement field of view.
[0043] In the load curve described in the present invention, the load curve is divided into a valley portion, a core portion, and a mountain portion, with the positions where the load area ratio is 10% and 80% being used as boundaries.
[0044] Reference Figure 1 , and at the same time corresponding to the surface treatment layer of the embodiment of the present invention, each parameter is explained. Vvv means the volume of the space part of the valley of the surface treatment layer, Vvc means the volume of the space part of the core of the surface treatment layer, Vmp means the volume of the entity part of the mountain of the surface treatment layer, and Vmc means the volume of the entity part of the core of the surface treatment layer. Sk means the level difference of the core of the surface treatment layer (the difference between the upper limit level and the lower limit level of the core), Spk means the average height of the mountain of the surface treatment layer, and Svk means the average depth of the valley of the surface treatment layer.
[0045] Furthermore, the so-called mountain part refers to the high part of the object to be measured. The so-called valley part refers to the low part of the object to be measured. The so-called core part refers to the part of the object to be measured other than the mountain part and the valley part, that is, the part close to the average height.
[0046] The solid volume Vmp of the peak portion of the surface treatment layer (hereinafter sometimes simply referred to as "Vmp") is related to the complexity of the shape of the surface treatment layer, and particularly to the complexity of the shape of the roughened particles constituting the roughened layer when the surface treatment layer includes a roughened layer.
[0047] As described above, in the surface-treated copper foil according to the embodiment of the present invention, the Vmp of the surface-treated layer is set to 0.010 to 0.080 μm. 3 / μm 2 If the Vmp is within this range, the anchoring effect of the surface treatment layer can be enhanced, thereby improving the adhesion between the surface treated copper foil and the resin substrate. In particular, if the Vmp of the surface treatment layer is 0.010 μm 3 / μm 2 If the Vmp of the surface treatment layer is 0.080 μm, the complexity of the surface treatment layer will be improved, and the desired anchoring effect can be obtained. 3 / μm 2 The transmission loss can be reduced.
[0048] From the viewpoint of stably improving the anchoring effect of the surface treatment layer, the Vmp of the surface treatment layer is preferably 0.020 to 0.060 μm 3 / μm 2 , more preferably 0.026 to 0.038 μm 3 / μm 2 .
[0049] The Zn adhesion of the surface treatment layer is 10 to 250 μg / dm 2 If the Zn coating amount is within this range, the solder heat resistance of the circuit pattern formed by the surface-treated copper foil can be improved. From the perspective of stably improving this effect, the Zn coating amount of the surface-treated layer is preferably 30 to 220 μg / dm 2 , more preferably 50 to 220 μg / dm 2 , and more preferably 82 to 200 μg / dm 2 .
[0050] The amount of Zn attached to the surface treatment layer can be measured by dissolving the surface treatment layer in 20% by mass nitric acid and using an atomic absorption spectrophotometer (manufactured by VARIAN, AA240FS) to perform quantitative analysis by atomic absorption method. When the surface treatment layer is provided on both sides of the copper foil, the surface of the surface treatment layer not to be measured is protected, and then the surface treatment layer to be measured is dissolved for quantitative analysis.
[0051] The type of the surface treatment layer is not particularly limited as long as the above-mentioned conditions of surface shape and Zn deposition amount are satisfied, and various surface treatment layers known in the technical field can be used.
[0052] Examples of the surface treatment layer include a roughening treatment layer, a chemical resistance treatment layer, a heat resistance treatment layer, a chromate treatment layer, a silane coupling treatment layer, etc. These layers can be used alone or in combination of two or more. Among them, from the viewpoint of adhesion to the resin substrate, the surface treatment layer preferably contains a roughening treatment layer.
[0053] When the surface treatment layer includes one or more layers selected from the group consisting of a chemical-resistant treatment layer, a heat-resistant treatment layer, a chromate treatment layer, and a silane coupling treatment layer, these layers are preferably provided on the roughening treatment layer.
[0054] The roughening treatment layer contains roughening particles. The roughening particles may also contain primary roughening particles and secondary roughening particles. The secondary roughening particles may also have a chemical composition different from that of the primary roughening particles. In addition, it is preferred that a covering plating layer is formed on at least a portion of the surface of the primary roughening particles.
[0055] Figure 2 This is a cross-sectional view schematically showing a surface-treated copper foil having a roughened layer on one surface of the copper foil.
[0056] like Figure 2 As shown, an example of an embodiment of the present invention includes a roughening layer formed on one side of a copper foil (10). The roughening layer contains primary roughening particles (20), a covering plating layer (30) covering the primary roughening particles (20), and secondary roughening particles (40) formed on the covering plating layer (30). Preferably, the primary roughening particles (20) covered by the covering plating layer (30) are roughly spherical, and the secondary roughening particles (40) are formed in a manner that expands into a dendrite. It is believed that the surface treatment layer with Vmp controlled to the above range has such a cross-sectional structure.
[0057] The roughened particles are not particularly limited, and may be formed of a single element selected from the group consisting of copper, nickel, cobalt, phosphorus, tungsten, arsenic, molybdenum, chromium, and zinc, or an alloy containing two or more of these elements.
[0058] The primary roughening particles are preferably made of copper or a copper alloy, and particularly made of copper.
[0059] The secondary roughened particles are preferably formed of an alloy containing copper, cobalt, and nickel.
[0060] The cover plating layer is not particularly limited, and can be formed of copper, silver, gold, nickel, cobalt, zinc, etc. Among them, the cover plating layer is preferably formed of copper.
[0061] The roughening treatment layer can be formed, for example, by performing a primary roughening treatment to form primary roughening particles, performing a covering plating to form a covering plating layer, and then performing a secondary roughening treatment to form secondary roughening particles. By performing the roughening treatment using this method, it is easy to form a surface treatment layer having a surface shape as described above.
[0062] The formation of each particle and layer can be performed by electroplating. Specifically, the primary roughened particles can be formed by electroplating using a plating solution to which a trace amount of tungsten compound is added. The cover plating layer and the secondary roughened particles can be formed by electroplating using a plating solution containing a predetermined component.
[0063] The tungsten compound is not particularly limited, and for example, sodium tungstate (Na 2 WO 4 )wait.
[0064] The content of tungsten compounds in the plating solution is preferably set to 1ppm or more. Sometimes, there are tiny recesses such as oil pits on the surface of the copper foil forming the roughening treatment layer, and the roughening particles around the recesses become too small or no roughening particles are formed. However, if this content is used, the overgrowth of the primary roughening particles formed on the relatively smooth part of the copper foil is suppressed, and the primary roughening particles are easily formed around the recesses. Furthermore, the upper limit of the content of tungsten compounds is not particularly limited, and from the perspective of suppressing the increase in resistance, it is preferably 20ppm.
[0065] The electroplating conditions for forming the roughening layer may be adjusted according to the electroplating apparatus used, etc., and are not particularly limited, but typical conditions are as follows. Each electroplating may be performed once or multiple times.
[0066] (Formation conditions of primary roughened particles)
[0067] Plating solution composition: 5-15 g / L Cu, 40-100 g / L sulfuric acid, 1-6 ppm sodium tungstate Plating solution temperature: 20-50 °C
[0068] Electroplating conditions: current density 30~90A / dm 2 , time 0.1~8 seconds
[0069] (Conditions for forming the covering plating layer)
[0070] Plating solution composition: 10-30 g / L Cu, 70-130 g / L sulfuric acid
[0071] Plating solution temperature: 30~60℃
[0072] Electroplating conditions: current density 4.8~15A / dm 2 , time 0.1~8 seconds
[0073] (Formation conditions of secondary roughened particles)
[0074] Plating solution composition: 10-20 g / L Cu, 5-15 g / L Co, 5-15 g / L Ni
[0075] Plating solution temperature: 30~50℃
[0076] Electroplating conditions: current density 24~50A / dm 2 , time 0.3~0.8 seconds
[0077] The chemical treatment resistant layer and the heat treatment resistant layer are not particularly limited and can be formed of materials known in the technical field. Furthermore, since the chemical treatment resistant layer sometimes also functions as a heat treatment resistant layer, a single layer having both functions of the chemical treatment resistant layer and the heat treatment resistant layer can be formed as the chemical treatment resistant layer and the heat treatment resistant layer.
[0078] The chemical treatment resistant layer and / or heat treatment resistant layer may be formed as a layer containing one or more elements selected from the group consisting of nickel, zinc, tin, cobalt, molybdenum, copper, tungsten, phosphorus, arsenic, chromium, vanadium, titanium, aluminum, gold, silver, platinum group elements, iron and tantalum (it may be in any form such as metal, alloy, oxide, nitride, sulfide, etc.). Among them, the chemical treatment resistant layer is preferably a Co-Ni layer. The heat treatment resistant layer is preferably a Ni-Zn layer.
[0079] The chemical-resistant layer and the heat-resistant layer can be formed by electroplating. The conditions can be adjusted according to the electroplating device used and are not particularly limited. The conditions for forming the chemical-resistant layer (Co-Ni layer) and the heat-resistant layer (Ni-Zn layer) using a conventional electroplating device are as follows. In addition, electroplating can be performed once or multiple times.
[0080] (Chemical-resistant layer: Formation conditions of Co-Ni layer)
[0081] Plating solution composition: 1-8 g / L Co, 5-20 g / L Ni
[0082] Plating solution pH: 2-3
[0083] Plating solution temperature: 40~60℃
[0084] Electroplating conditions: current density 1~20A / dm 2 , time 0.3~0.6 seconds
[0085] (Heat-resistant treatment layer: Formation conditions of Ni-Zn layer)
[0086] Plating solution composition: 1~30g / L Ni, 1~30g / L Zn
[0087] Plating solution pH: 2~5
[0088] Plating solution temperature: 30~50℃
[0089] Electroplating conditions: current density 0.1~10A / dm 2 , time 0.1~5 seconds
[0090] The chromate treatment layer is not particularly limited, and can be formed of a material known in the technical field.
[0091] Here, in this specification, the "chromate-treated layer" means a layer formed from a liquid containing chromic anhydride, chromic acid, dichromic acid, chromate or dichromate.
[0092] The chromate treatment layer may be formed as a layer containing one or more elements selected from the group consisting of cobalt, iron, nickel, molybdenum, zinc, tantalum, copper, aluminum, phosphorus, tungsten, tin, arsenic and titanium (may be in any form such as metal, alloy, oxide, nitride, sulfide, etc.). Examples of the chromate treatment layer include a chromate treatment layer treated with an aqueous solution of chromic anhydride or potassium dichromate, and a chromate treatment layer treated with a treatment solution containing chromic anhydride or potassium dichromate and zinc.
[0093] The chromate treatment layer can be formed by known methods such as immersion chromate treatment and electrolytic chromate treatment. The conditions of these methods are not particularly limited. For example, the conditions for forming a common chromate treatment layer are as follows. In addition, the chromate treatment may be performed once or multiple times.
[0094] Chromate solution composition: 1-10 g / L K 2 Cr 2 O 7 , 0.01~10g / L Zn
[0095] Chromate solution pH: 2-5
[0096] Chromate solution temperature: 30~55℃
[0097] Electrolysis conditions: current density 0.1~10A / dm 2 , time 0.1 to 5 seconds (in the case of electrolytic chromate treatment)
[0098] The silane coupling treatment layer is not particularly limited, and can be formed of a material known in the technical field.
[0099] Here, in this specification, the "silane coupling treatment layer" means a layer formed of a silane coupling agent.
[0100] The silane coupling agent is not particularly limited, and any silane coupling agent known in the technical field can be used. Examples of the silane coupling agent include amino silane coupling agents, epoxy silane coupling agents, mercapto silane coupling agents, methacryloxy silane coupling agents, vinyl silane coupling agents, imidazole silane coupling agents, triazine silane coupling agents, etc. Among them, amino silane coupling agents and epoxy silane coupling agents are preferred. The above silane coupling agents can be used alone or in combination of two or more.
[0101] A typical method for forming the silane coupling treatment layer is to apply a 1 to 3 volume % aqueous solution of the above-mentioned silane coupling agent and then dry the solution to form the silane coupling treatment layer.
[0102] The copper foil is not particularly limited, and may be either an electrolytic copper foil or a rolled copper foil.
[0103] Electrolytic copper foil is usually produced by electrolytically depositing copper from a copper sulfate plating bath onto a titanium or stainless steel drum, and has a flat S surface (glossy surface) formed on the drum side and an M surface (matte surface) on the opposite side of the formed S surface. The M surface of the electrolytic copper foil usually has tiny concavoconvex parts. In addition, the S surface of the electrolytic copper foil has tiny concavoconvex parts due to the transfer of grinding stripes of the drum formed during grinding.
[0104] The rolled copper foil has minute irregularities on its surface due to the formation of oil pits caused by rolling oil during rolling.
[0105] The material of the copper foil is not particularly limited. When the copper foil is a rolled copper foil, high-purity copper such as refined copper (JIS H3100 alloy number C1100) or oxygen-free copper (JIS H3100 alloy number C1020 or JIS H3510 alloy number C1011) commonly used for circuit patterns of printed circuit boards can be used. In addition, for example, copper alloys such as Sn-doped copper, Ag-doped copper, copper alloys added with Cr, Zr or Mg, and Casson-based copper alloys added with Ni and Si can also be used. In addition, in this specification, the concept of "copper foil" also includes copper alloy foil.
[0106] In the case where the copper foil is a rolled copper foil, the rolled copper foil may also have a composition containing 99.0% by mass or more of Cu and 0.003% to 0.825% by mass of one or more elements selected from the group consisting of P, Ti, Sn, Ni, Be, Zn, In and Mg, and the remainder is composed of inevitable impurities. In addition, the rolled copper foil may also have a composition containing 99.9% by mass or more of Cu and 0.0005% to 0.0220% by mass of P, and the remainder is composed of inevitable impurities. Furthermore, the rolled copper foil may also have a composition containing 99.0% by mass or more of Cu, and the remainder is composed of inevitable impurities.
[0107] Moreover, when the copper foil is a rolled copper foil, the average crystal grain size may be 0.5 to 4.0 μm, and the tensile strength in the rolling direction may be 235 to 290 MPa.
[0108] Furthermore, the rolled copper foil may have an electrical conductivity of 75% IACS or more. The electrical conductivity of the copper foil can be measured at room temperature (25° C.) by a four-terminal method in accordance with JIS H0505 (1975).
[0109] The thickness of the copper foil is not particularly limited, and may be, for example, 1 to 1000 μm, 1 to 500 μm, 1 to 300 μm, 3 to 100 μm, 5 to 70 μm, 6 to 35 μm, or 9 to 18 μm.
[0110] The surface treated copper foil having the above-mentioned structure can be manufactured according to a method known in the art. Here, the surface property parameters such as Vmp of the surface treated layer can be controlled by adjusting the formation conditions of the surface treated layer, especially the formation conditions of the above-mentioned roughening treatment layer. In addition, the Zn adhesion amount of the surface treated layer can be controlled by adjusting the type of the surface treated layer.
[0111] The surface treated copper foil of the embodiment of the present invention controls the Vmp of the surface treated layer to 0.010 to 0.080 μm. 3 / μm 2 , the Zn adhesion amount is controlled to 10~250μg / dm 2 , so it is possible to improve the adhesion with a resin substrate, especially a resin substrate suitable for high-frequency applications, and form a circuit pattern with excellent solder heat resistance.
[0112] A copper-clad laminate according to an embodiment of the present invention includes the surface-treated copper foil and a resin base material of a surface-treated layer that adheres to the surface-treated copper foil.
[0113] The copper-clad laminate can be produced by bonding a resin substrate to the surface-treated layer of the surface-treated copper foil.
[0114] The resin substrate is not particularly limited, and any resin substrate known in the technical field can be used. Examples of the resin substrate include paper-based phenolic resin, paper-based epoxy resin, synthetic fiber cloth-based epoxy resin, glass cloth / paper composite-based epoxy resin, glass cloth / glass non-woven composite-based epoxy resin, glass cloth-based epoxy resin, polyester film, polyimide resin, liquid crystal polymer, fluororesin, etc. Among them, the resin substrate is preferably a polyimide resin.
[0115] In addition, as a resin substrate particularly suitable for high-frequency applications, a resin substrate formed of a low-dielectric material can be cited. Examples of low-dielectric materials include liquid crystal polymers, low-dielectric polyimides, fluororesins, etc. The low-dielectric material can also be a material having a dielectric constant of 3.5 or less at 1 MHz. As a low-dielectric material suitable for high-frequency applications, a material having a dielectric constant of 3.4 or less at 30 GHz can also be cited.
[0116] The bonding method between the surface-treated copper foil and the resin substrate is not particularly limited, and can be carried out according to a method known in the art. For example, the surface-treated copper foil and the resin substrate may be laminated and then thermally compressed.
[0117] The copper-clad laminate produced in the above manner can be used to produce a printed wiring board.
[0118] Since the copper-clad laminate according to the embodiment of the present invention uses the surface-treated copper foil, it has excellent adhesion to a resin substrate, especially a resin substrate suitable for high-frequency applications, and can form a circuit pattern with excellent solder heat resistance.
[0119] A printed wiring board according to an embodiment of the present invention includes a circuit pattern formed by etching the surface-treated copper foil of the copper-clad laminate.
[0120] The printed wiring board can be produced by etching the surface-treated copper foil of the copper-clad laminate to form a circuit pattern.
[0121] The method for forming the circuit pattern is not particularly limited, and known methods such as a subtractive method and a semi-additive method can be used. Among them, the method for forming the circuit pattern is preferably a subtractive method.
[0122] When a printed wiring board is manufactured by a subtractive method, it is preferably carried out in the following manner. First, a resist is applied to the surface of the surface-treated copper foil of the copper-clad laminate, and then exposed and developed to form a predetermined resist pattern. Next, a circuit pattern is formed by etching away the surface-treated copper foil where the resist pattern is not formed (i.e., the excess portion). Finally, the resist pattern on the surface-treated copper foil is removed.
[0123] In addition, various conditions in this subtractive method are not particularly limited, and it can be carried out according to conditions known in the technical field.
[0124] The printed wiring board according to the embodiment of the present invention uses the copper-clad laminate and therefore has a circuit pattern with excellent solder heat resistance, and has excellent adhesion between the resin substrate, especially a resin substrate suitable for high-frequency applications, and the circuit pattern.
[0125] [Example]
[0126] Hereinafter, the embodiments of the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples at all.
[0127] (Example 1)
[0128] Prepare a rolled copper foil with a thickness of 12 μm (HG foil manufactured by JX Metals Co., Ltd.). After degreasing and pickling both sides of the copper foil, a surface-treated copper foil is obtained by sequentially forming a roughened layer, a chemical-resistant treatment layer (Co-Ni layer), a chromate treatment layer, and a silane coupling treatment layer on one side (hereinafter referred to as the "first side") as the surface treatment layer.
[0129] The formation conditions of each treatment layer are as follows.
[0130] (1) Roughened layer / first side
[0131] <Formation conditions of primary roughened particles>
[0132] Plating solution composition: 12 g / L of Cu, 50 g / L of sulfuric acid, 5 ppm of tungsten (from sodium tungstate dihydrate)
[0133] Plating solution temperature: 27 °C
[0134] Electroplating conditions: Current density 39.5 A / dm 2 , time 1.2 seconds
[0135] Number of electroplating treatments: 2 times
[0136] <Formation conditions of overplated layer>
[0137] Plating solution composition: 20 g / L of Cu, 100 g / L of sulfuric acid
[0138] Plating solution temperature: 50 °C
[0139] Electroplating conditions: Current density 9.6 A / dm 2 , time 1.8 seconds
[0140] Number of electroplating treatments: 2 times
[0141] <Formation conditions of secondary roughened particles>
[0142] Plating solution composition: 15.5 g / L of Cu, 7.5 g / L of Co, 9.5 g / L of Ni
[0143] Plating solution temperature: 50 °C
[0144] Electroplating conditions: Current density 33.3 A / dm 2 , time 0.55 seconds
[0145] Number of electroplating treatments: 2 times
[0146] (2) Chemical-resistant treatment layer / first side
[0147] <Formation conditions of Co-Ni layer>
[0148] Plating solution composition: 3g / L Co, 13g / L Ni
[0149] Plating solution pH: 2.0
[0150] Plating solution temperature: 50°C
[0151] Electroplating conditions: current density 4.5A / dm 2 , time 0.48 seconds
[0152] Electroplating times: 1 time
[0153] (3) Chromate treatment layer / 1st surface
[0154] <Conditions for forming the electrolytic chromate treatment layer>
[0155] Chromate solution composition: 3g / L K 2 Cr 2 O 7 , 0.33 g / L Zn
[0156] Chromate solution pH: 3.7
[0157] Chromate solution temperature: 55°C
[0158] Electrolysis conditions: current density 0.64A / dm 2 , time 0.90 seconds
[0159] Chromate treatment times: 2 times
[0160] (4) Silane coupling treatment layer / first surface
[0161] A silane coupling treatment layer was formed by applying a 1.2 volume % aqueous solution of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane and drying the solution.
[0162] (Example 2)
[0163] In the formation conditions of the chromate treatment layer on the first surface, the electroplating conditions were changed to a current density of 1.0 A / dm 2 , a surface-treated copper foil was obtained using the same conditions as in Example 1 except for the above.
[0164] (Example 3)
[0165] In the formation conditions of the chromate treatment layer on the first surface, the electroplating conditions were changed to a current density of 1.4 A / dm 2 , a surface-treated copper foil was obtained using the same conditions as in Example 1 except for the above.
[0166] (Comparative Example 1)
[0167] A surface-treated copper foil was obtained under the same conditions as in Example 1 except that the foil was immersed in the chromate solution without applying a current in the formation conditions of the chromate treatment layer on the first surface.
[0168] The following evaluations were performed on the surface-treated copper foils obtained in the above-mentioned Examples and Comparative Examples.
[0169] <Measurement of Zn Adhesion Amount in Surface Treatment Layer (First Surface)>
[0170] The amount of Zn deposited in the surface treatment layer (first surface) was measured by dissolving the surface treatment layer (first surface) in 20 mass % nitric acid and performing quantitative analysis by an atomic absorption method using an atomic absorption spectrophotometer (AA240FS manufactured by VARIAN).
[0171] <Vmp of surface treatment layer (first surface)>
[0172] The images were taken using a laser microscope (LEXT OLS4000) manufactured by Olympus Corporation. The images were analyzed using the analysis software of a laser microscope (LEXT OLS4100) manufactured by Olympus Corporation. The Vmp of the surface treatment layer was measured in accordance with ISO 25178-2:2012. The measurement result was the average value of the values measured at any 10 locations. The temperature during the measurement was set at 23 to 25°C.
[0173] The main setting conditions in the laser microscope and analysis software are as follows.
[0174] Objective lens: MPLAPON50XLEXT (magnification: 50x, numerical aperture: 0.95, immersion type: air, mechanical barrel length: ∞, cover glass thickness: 0, field of view: FN18)
[0175] Optical zoom ratio: 1x
[0176] Scanning mode: XYZ high precision (height resolution: 60nm, number of pixels of input data: 1024×1024)
[0177] Input image size [number of pixels]: 257 μm x 258 μm [1024 x 1024]
[0178] (Since the measurement is performed in the horizontal direction, the evaluation length is equivalent to 257 μm)
[0179] DIC: Off
[0180] Multilayer: Off
[0181] Laser Strength: 100
[0182] Offset: 0
[0183] Confocal level: 0
[0184] Beam Diameter Aperture: Close
[0185] Image averaging: 1 time
[0186] Noise Reduction: On
[0187] Uneven brightness correction: On
[0188] Optical Noise Filter: On
[0189] Cut-off: λc=200μm, no λs and λf
[0190] Filter: Gaussian filter
[0191] Noise Removal: Pre-Assay Processing
[0192] Surface (tilt) correction: implemented
[0193] Brightness: Adjust to a range of 30 to 50
[0194] The brightness is a value that should be appropriately set according to the color tone of the measurement object. The above setting is suitable for measuring the surface of the surface-treated copper foil having L* of -69 to -10, a* of 2 to 32, and b* of 2 to 21.
[0195] <Measurement of Hue of Measurement Object>
[0196] MiniScan (registered trademark) EZ Model 4000L manufactured by HunterLab was used as a measuring instrument to measure L*, a* and b* of the CIE L*a*b* colorimetric system in accordance with JIS Z8730:2009. Specifically, the measuring object surface of the surface-treated copper foil obtained in the above-mentioned embodiment and comparative example was pressed against the photosensitive part of the measuring instrument so that light could not enter from the outside. In addition, the measurement of L*, a* and b* was performed based on the geometric condition C of JIS Z8722:2009. In addition, the main conditions of the measuring instrument are as follows.
[0197] Optical system: d / 8°, integrating sphere size: 63.5mm, observation light source: D65
[0198] Measurement method: Reflection
[0199] Illumination diameter: 25.4mm
[0200] Measuring diameter: 20.0mm
[0201] Measurement wavelength / interval: 400~700nm / 10nm
[0202] Light source: Pulse xenon lamp / 1 light emission / measurement
[0203] Traceability standards: Based on CIE 44 and ASTM E259, calibrated by the National Institute of Standards and Technology (NIST)
[0204] Standard observer: 10°
[0205] The white tiles used as the measurement reference used the following object colors.
[0206] When measured at D65 / 10°, the values in the CIE XYZ colorimetric system are X: 81.90, Y: 87.02, Z: 93.76
[0207] <Peel Strength>
[0208] After the surface treated copper foil (the first side) is bonded to the resin substrate formed by the low dielectric material, a circuit with a width of 3 mm is formed in the MD direction (the long side direction of the rolled copper foil). The formation of the circuit is implemented according to the usual method. Secondly, the strength (MD180° peel strength) when the circuit (surface treated copper foil) is peeled off at a speed of 50 mm / min in the 180° direction (i.e., the MD direction) relative to the surface of the resin substrate is measured according to JIS C6471:1995. The measurement is carried out 5 times, and its average value is used as the result of the peel strength. If the peel strength is 0.60 kgf / cm or more, it can be said that the adhesion between the circuit (surface treated copper foil) and the resin substrate is good.
[0209] <Solder Heat Resistance>
[0210] After the surface-treated copper foil is laminated to a resin substrate formed of a low-dielectric material, etching is performed in such a manner that the surface of the surface-treated copper foil becomes 25 mm × 25 mm. The formation of the circuit is carried out in accordance with the usual method. Secondly, the sample is placed in a constant temperature and humidity machine and maintained at a temperature of 85°C and a relative humidity of 85% for 48 hours. Then, the sample is floated in a solder tank containing solder at a specified temperature for 30 seconds and then taken out to visually confirm whether bubbles are generated in the circuit of the sample. When bubbles are not generated in the circuit of the sample, other samples are prepared, the temperature of the solder in the solder tank is increased, and it is confirmed again whether bubbles are generated in the circuit of the sample. Repeat this operation until bubbles are generated in the circuit of the sample. The result of this evaluation is represented by the highest temperature of the solder that does not generate bubbles in the circuit of the sample. If the highest temperature of the solder that does not generate bubbles in the circuit of the sample is above 300°C, it can be said that the heat resistance of the solder is good.
[0211] Table 1 shows the results of the above-mentioned property evaluations.
[0212] [Table 1]
[0213]
[0214] As shown in Table 1, the Vmp of the surface treatment layer is 0.010 to 0.080 μm 3 / μm 2 , Zn adhesion is between 10 and 250 μg / dm 2 The surface treated copper foils of Examples 1 to 3 within the range of have high peel strength and high solder maximum temperature (also good solder heat resistance).
[0215] On the other hand, since the surface-treated copper foil of Comparative Example 1 had too little Zn deposition amount, the solder maximum temperature became low (solder heat resistance was insufficient).
[0216] According to the above results, it can be seen that according to an embodiment of the present invention, a surface-treated copper foil can be provided, which can improve the adhesion with a resin substrate, especially a resin substrate suitable for high-frequency applications, and form a circuit pattern with excellent solder heat resistance. In addition, according to an embodiment of the present invention, a copper-clad laminate can be provided, wherein the adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and a surface-treated copper foil is excellent, and a circuit pattern with excellent solder heat resistance can be formed. Furthermore, according to an embodiment of the present invention, a printed wiring board can be provided, which has a circuit pattern with excellent solder heat resistance, and the adhesion between a resin substrate, especially a resin substrate suitable for high-frequency applications, and the circuit pattern is excellent.
[0217] Therefore, the present invention can be implemented as the following examples. [1]
[0219] A surface-treated copper foil comprises a copper foil and a surface-treated layer formed on at least one side of the copper foil.
[0220] The volume Vmp of the substantial part of the peak portion of the surface treatment layer is 0.010 to 0.080 μm 3 / μm 2 , and the Zn adhesion is 10~250μg / dm 2 . [2]
[0222] The surface-treated copper foil as described in [1], wherein the volume Vmp of the solid part of the peak portion is 0.020 to 0.060 μm 3 / μm 2 . [3]
[0224] The surface-treated copper foil as described in [2], wherein the volume Vmp of the solid part of the peak portion is 0.026 to 0.038 μm3 / μm 2 . [4]
[0226] The surface-treated copper foil according to any one of [1] to [3], wherein the amount of Zn deposited is 30 to 220 μg / dm 2 . [5]
[0228] The surface treated copper foil as described in [4], wherein the Zn adhesion amount is 50 to 220 μg / dm 2 . [6]
[0230] The surface treated copper foil as described in [5], wherein the Zn adhesion amount is 82 to 200 μg / dm 2 . [7]
[0232] The surface-treated copper foil according to any one of [1] to [6], wherein the surface-treated layer includes a roughening-treated layer. [8]
[0234] A copper-clad laminate comprising the surface-treated copper foil according to any one of [1] to [7] and a resin substrate of the surface-treated layer that is continuous with the surface-treated copper foil. [9]
[0236] A printed wiring board having a circuit pattern formed by etching the surface-treated copper foil of the copper-clad laminate described in [8].
[0237] Description of Reference Numerals
[0238] 10: Copper foil
[0239] 20: 1 time coarsening particles
[0240] 30: Covering plating layer
[0241] 40: Secondary coarsening of particles
Claims
1. A surface-treated copper foil comprising a copper foil and a surface-treated layer formed on at least one side of the copper foil, Regarding the surface treatment layer, the volume Vmp of the substantial part of the peak portion is 0.010 to 0.080 μm 3 / μm 2 , and the Zn adhesion is 10~250μg / dm 2 .
2. The surface-treated copper foil according to claim 1, wherein The volume Vmp of the solid part of the mountain is 0.020 to 0.060 μm 3 / μm 2 .
3. The surface-treated copper foil according to claim 2, wherein: The volume Vmp of the solid part of the mountain is 0.026 to 0.038 μm 3 / μm 2 .
4. The surface-treated copper foil according to claim 1, wherein The Zn adhesion amount is 30 to 220 μg / dm 2 .
5. The surface-treated copper foil according to claim 4, wherein The Zn adhesion amount is 50 to 220 μg / dm 2 .
6. The surface-treated copper foil according to claim 5, wherein: The Zn attachment amount is 82 to 200 μg / dm 2 .
7. The surface-treated copper foil according to any one of claims 1 to 6, wherein The surface treatment layer includes a roughening treatment layer. 8 . A copper-clad laminate comprising the surface-treated copper foil according to claim 1 , and a resin substrate of the surface-treated layer that is continuous with the surface-treated copper foil. 9 . A printed wiring board comprising a circuit pattern formed by etching the surface-treated copper foil of the copper-clad laminate according to claim 8 .
Citation Information
Patent Citations
Copper foil, and method for producing copper foil
JP2012112009A